MACAM MACAM MODEL KEPEMIMPINAN PESANTREN DI JAWA TIMUR - Aisyah Khoirunni'mah Al Mufarriju; Ainun Jariyah; Ayu Annisa; Rita Devita (Konsorsium Dosen Sekolah Tinggi Agama Islam (STAI) Al-Yasini Pasuruan, 2020)
This research is a library research that aims to describe 3 Islamic boarding schools in East Java with different leadership systems, in terms of how to decide on leadership changes in the pesantren. The pesantren is exactly in Bangil, Pasuruan has a leadership system that is hereditary, modern Islamic boarding school Babussalam Mojokerto village that implements a democratic system and pesantren Wildanusholihin applies in the decisions of the foundation. Leadership is an effort made by a leader together with its members to achieve the goals, vision and mission set in an institution or organization. The figure of the leader in each institution is certainly needed as a motivator or motivator, leader, director and mobilizer of members so that the institution they lead is well implemented. Education in Islamic boarding schools is known and recognized by the community as personality building education by emphasizing Islamic morals as a way of life in society. To achieve the goal of establishing the pesantren, leadership is certainly needed in each pesantren according to the leadership system applied by each. Keywords: Leadership Model, Islamic Boarding School